Das thermische Verhalten von Na5[Fe(CN)5SO3]·2H2O - Olabe Iparraguirre, José Antonio (1975)
The thermal behaviour of Na5[Fe(CN)5SO3]·2H2O has been investigated by thermogravimetric and differential thermal analysis. Detailed studies of the decomposition residues using various physicochemical methods show that decomposition occurs in a manner similar to that previously postulated for related compounds.